Criticizing the Verdict of 18/JN/2016/MS.MBO of Mahkamah Syar’iyah Meulaboh Aceh on Sexual Abuse against Children from the Perspective of Restorative Justice - Muhammad Siddiq Armia; Zahlul Pasha Karim; A. Hamid Sarong; Muhammad Zulhilmi; Muhammad Syauqi Bin-Armia (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This article is based on a critical review of the judgment in the Indonesian Islamic Court, known publicly as Mahkamah Syar’iyah, case number 18/JN/2016/MS.MBO. The tribunal process in the Indonesian legal system should present clear evidence that convinces all involved parties, including for sexual abuse cases. Unfortunately, during the tribunal process of the case, the judges had neither asked the prosecutor to show the evidence nor asked how the case had happened. After asking a few simple questions, judges have made consideration and finally a judgment. Two main research questions will be answered in this article; how is restorative justice applied for law-breaking cases in Acehnese view? Why has the punishment been imposed by the Mahkamah Syar'iyah in its legal considerations for the case? This article has used the black-letter law method and interview. The research results have indicated that the case seems weird and does not provide the due process of law principle. The tribunal procedure has not provided any sufficient evidence before the verdict had been decided. The connection between both evidence and judicial facts, in this case, is very blurred. The witness was simply based on the victim's evidence.